Analysis of The Influence of Ownership of Marine And Fisheries Business Actor Cards On The Welfare of Fishermen In Juru Banu Village Based On The Calculation of The Fishermen’s Exchange Rate - Maulana Ihsan; Emmy Sri Mahreda; Irma Febrianty (International Journal of Science and Environment (IJSE), 2026)
Fishermen's welfare can be seen from the ability of fishing households to meet their basic needs, including food, education, health, housing, and production needs. This study aims to analyze the effect of ownership of a marine and fisheries business actor card on the welfare of fishermen in Juru Banu village based on calculations of the fishermen's exchange rate. This research will be conducted in Juru Banu village, Paju Epat sub-district, East Barito Regency, Central Kalimantan Province. The research sample consists of 63 respondents. The data analysis technique used simple linear regression analysis. The results of the simple regression analysis indicate that ownership of a marine and fisheries business actor card can affect the welfare of fishermen in Juru Banu village by 57.3% based on the fishermen's exchange rate. Meanwhile, 42.7% is influenced by other factors not examined in this study. The variable of ownership of a marine and fisheries business actor card has a significant effect of 99% on fishermen's welfare based on the fishermen's exchange rate calculation and has a positive direction. This means that if one additional fisherman owns a marine and fisheries business actor card, fishermen's welfare based on the fishermen's exchange rate calculation will increase by 0.350 units.